THE IMPORTANCE OF SOCIOLINGUISTICS IN LANGUAGE TEACHING - Dustqulova Munira Shokir kizi (International Engineering Journal For Research & Development, 2022)
Teaching process is closely connected with sociolinguistics in numerous ways, especially teaching a new language and different branches of sociolinguistics have had sensible influence on second lan-guage teaching. Since the late 1960s sociolinguistics have paid their attention on how language is used appropriately in different contexts. So that, this paper will deal with communicative approach that is founded on the basis of communicative competence also this work argues that the most significant role of sociolinguistics in language teaching is to explain the learners with the appropriate rules of speaking and writing and raise their sociolinguistics awareness .Hopefully ,this research will be an instruction for readers and it can also be a plan while learning in real life.